The construction of a spiritual management: A social change perspective (International Journal of Psychosocial Rehabilitation, 2020)
Implementation of management in a company can be deteriorated due to some reasons such as miscommunication, untreatable and un-trustable among the human resources. Management of a company, certainly, leads to the point of changing because of the social interaction change. Therefore, the misconception of management will not work and will affect the chain management of the company. Finally, it will not be fruitful and will lead to high tension. As a result, the Christian’s values should be considered as the entrance point to construct a spiritual management approach to revive and build the concept of management in a company. One of the examples being taken is the small company in Indonesian territory to be analysed, where the spiritual management is built from the owners whom they are coming from different faiths. Overall, some elements are found to construct spiritual management in the pattern of Christian’s values.